1993
DOI: 10.1007/bf02374471
|View full text |Cite
|
Sign up to set email alerts
|

Decreased skin blood flow early in the course of streptozotocin-induced diabetes mellitus in the rat

Abstract: We have previously used laser Doppler technology to demonstrate that skin blood flow is reduced in Type 1 (insulin-dependent) diabetic patients. The possibility of using the skin as an extremely accessible indicator of diabetic microvascular disease is attractive. The streptozotocin diabetic rat is an appealing potential animal model. We performed measurements of skin blood flow in two rat species, nine Sprague Dawley (SD) rats and nine Wistar Kyoto (WKY) rats, observing early changes following the inception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…Diabetic wounds tended to exhibit less bleeding, implying a defect in the peripheral circulation, consistent with the findings of Rendell et al, 7 who showed that skin blood flow early in the streptozotocin-induced diabetic rats was decreased by 30-40%. The defect of micro-circulation in the skin and subcutaneous tissue impairs wound healing through the decreased delivery of nutrients, oxygen, and immune cells to initiate and sustain the reparatory process.…”
Section: Discussionsupporting
confidence: 85%
“…Diabetic wounds tended to exhibit less bleeding, implying a defect in the peripheral circulation, consistent with the findings of Rendell et al, 7 who showed that skin blood flow early in the streptozotocin-induced diabetic rats was decreased by 30-40%. The defect of micro-circulation in the skin and subcutaneous tissue impairs wound healing through the decreased delivery of nutrients, oxygen, and immune cells to initiate and sustain the reparatory process.…”
Section: Discussionsupporting
confidence: 85%
“…The prolongation of inflammatory response was consistent with the findings of Wetzler et al 6 that macrophage-inflammatory protein-2/mRNA together with the macrophage-chemoattractant-protein-1/ mRNA expressions were extended and directly associated with sustained infiltration, but with different localization of PMN and macrophages in the diabetic wound. It was also found out by Rendell et al 7 that skin blood flow early in the streptozotocin-induced diabetic rats was decreased by 30-40% as a function of time paralleling the increase in glycated hemoglobin. This defect in microcirculation leads to the delay of inflammatory cells reaching the burn site, aggravated by the blocking of capillaries (by coagulated proteins and cellular debris) that needs to be cleared out.…”
Section: Discussionsupporting
confidence: 50%
“…In the present study, LY333531 treatment corrected thermal hyperalgesia without having any effect on mechanical thresholds, which suggests a specific action rather than a general anti-allodynic or central analgesic effect. The thermal anti-nociceptive action could relate to increased nerve\ganglion blood flow or to improvements in skin perfusion in the vicinity of sensory nerve terminals [43], a hypothesis that is testable using peripheral vasodilator treatment. The lack of an effect on mechanical nociception thresholds, which are correctable with insulin treatment [40], suggests that a PKCβ-mediated vascular mechanism is not critically important.…”
Section: Discussionmentioning
confidence: 99%